Exploring the Relationship Between Language Learning Strategies, Academic Achievement, Grade Level, and Gender - Senad Bećirović; Amna Brdarević-Čeljo; Edda Polz (National Research University Higher School of Economics, 2021)
Learning efficacy can be substantially improved through the frequent use of learning strategies, whose practicality has been confirmed through extensive research. Thus, the purpose of the current study is to contribute to this wealth of research by determining whether learning strategies are significant predictors of students' achievement in learning English as a foreign language (EFL) as well as by exploring strategy awareness and variations in strategy use by gender, grade level, and overall grade point average (GPA) among 206 high school students. The results indicated that cognitive strategies are significant positive predictors, while memory and affective strategies are significant negative predictors of students' achievement in foreign language learning. Moreover, the findings revealed a significant impact of overall GPA and an insignificant impact of gender and grade level on the use of strategy subtypes, with the most frequently used strategies being metacognitive and the least frequently used being affective strategies. Furthermore, this research highlights the importance of incorporating strategies-based instruction methods into foreign language curriculums in the Bosnian context and also aims to raise teachers' awareness of the importance of their application in the classroom milieu